Increased 30-day mortality associated with weekend emergency admission for alcohol-related liver disease in England: a record-linkage study using the Clinical Practice Research Datalink - Keith Bodger; Susanna Dodd; Thomas Mair; Steve Hood; Kate M Fleming; Benjamin Silberberg; Pietà Schofield; William Tench (BMJ Open Gastroenterology)
Objective Deficiencies have been highlighted in acute hospital care for alcohol-related liver disease (ARLD). Such problems may be worse at weekends (WEs). Increased 30-day mortality for WE admissions has been reported for several acute conditions, but data for ARLD are limited. We aimed to compare patient and pathway characteristics between WE and weekday (WD) admissions and investigate the ‘weekend effect’ on mortality.Methods Retrospective cohort study (2008–2018) using linked electronic databases (Hospital Episode Statistics-Clinical Practice Research Datalink and death registration) including 17 575 first emergency admissions identified using the Liverpool ARLD algorithm. Exposure: WE admission (Saturday or Sunday). Main outcome: all-cause death within 30 days. Covariates included socio-demographic characteristics, pathway characteristics (pre-admission contacts and admission method) and markers of severity (recorded stage of liver disease, ascites and varices, comorbidity). Alternative risk-adjustment methods were used, including standard regression and propensity-weighted analysis (Inverse Probability of Treatment Weighting).Results 3249 admissions (18.5%) were at WE. Unadjusted 30-day mortality was significantly higher for WE versus WD (17.1% vs 15.5%, p=0.018). All models demonstrated increased odds of death for WE admissions with adjusted ORs ranging from 1.15 to 1.23 (relative risk of 1.12–1.19). Causes of death did not vary by admission day and effect was consistent across subgroups. Findings were robust to sensitivity analyses restricting the cohort to patients admitted directly from Accident and Emergency department (A&E), or cirrhosis or ascites but not varices.Conclusion First ARLD admissions at the WE experienced a 12–19% increase in 30-day mortality risk compared with WD. Although residual confounding cannot be excluded, this suggests the possibility of avoidable mortality among those hospitalised at WEs. Services should be alert to risks of WE effects when planning care.